2014
DOI: 10.2147/cia.s69673
|View full text |Cite
|
Sign up to set email alerts
|

Does a Wii-based exercise program enhance balance control of independently functioning older adults? A systematic review

Abstract: BackgroundExercise programs that challenge an individual’s balance have been shown to reduce the risk of falls among older adults. Virtual reality computer-based technology that provides the user with opportunities to interact with virtual objects is used extensively for entertainment. There is a growing interest in the potential of virtual reality-based interventions for balance training in older adults. This work comprises a systematic review of the literature to determine the effects of intervention program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
4
25

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 54 publications
4
86
4
25
Order By: Relevance
“…However, Rodrigues et al11 contradicted the results of Laufer et al10 Rodrigues et al aimed to evaluate the effect of exergaming on musculoskeletal function among the elderly. An important point is that they included both healthy and unhealthy people in their sample of participants.…”
Section: Introductionmentioning
confidence: 99%
“…However, Rodrigues et al11 contradicted the results of Laufer et al10 Rodrigues et al aimed to evaluate the effect of exergaming on musculoskeletal function among the elderly. An important point is that they included both healthy and unhealthy people in their sample of participants.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, this literature review clearly suggests that most researchers were interested in the improvement of fitness because physical inactivity among adults (e.g., Bonetti, Drury, Danoff, & Miller, 2010;Diest et al, 2013) and children is a major contributor to diseases associated with obesity (World Health Organization, 2010). There was a great number of studies that have investigated AVGs participation in PA and its positive effects in reducing the risk of obesity (e.g., Maloney, Threlkeld, & Cook, 2012;Goersch et al, 2013), hypertension (e.g., Chen & Wilkosz, 2014), congestive heart failure (e.g., Klompstra, Jaarsma, & Strömberg, 2014;Tripette et al, 2014), atherosclerosis (e.g., Laufer, Dar, & Kodesh, 2014) and cardiovascular disease (e.g., Thompson, Gordon, & Pescatello, 2010). Controlled studies also showed that active video games increased capacities in relation to PA and education (Hammond, Jones, Hill, Green, & Male, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of such technology for the prevention of falls has been limited due to the scarcity of studies which used virtual reality to train the balance and prevent falls in the elderly (19) . However, some studies showed the importance of inclusion of this modality in the treatment of balance disorders in elderly (13,19,20) . The present study aimed to verify in the literature the relation of the benefits of virtual reality in the postural balance of healthy elderly people.…”
Section: Group Control: Received Only Pretest Measurements and Evaluamentioning
confidence: 99%